IoT-Based Community Smart Health Service Model: Empowering Entrepreneurs in Health Innovation - Jonas, Dendy; Purnomo, Hindriyanto Dwi; Iriani, Ade; Sembiring, Irwan; Kristiadi, Dedy Prasetya; Nanle, Zeze (Pandawan, 2025)
The Indonesian government aims to improve public health by integrating a unified health platform with regional systems for effective decision-making. However, the existing health information system is inadequate for broader decision-making needs, focusing primarily on individuals with existing health issues and not adequately addressing the needs of disaster victims, such as those affected by floods, accidents, and burns. Tangerang City, located in Banten Province, is a flood-prone area that faces annual disasters, highlighting this gap. To address this issue, this study proposes the development of a Health Internet of Things (HIoT) model designed to support rapid decision-making and enhance community health services. The proposed IoT-based network will be implemented in residential complexes, private clinics, schools, and places of worship, enabling real-time monitoring of health conditions and facilitating disaster or pandemic mitigation. Data collected from these communities will be transmitted to nearby hospitals for immediate medical assistance. Preliminary findings suggest that the IoT-based e-health system offers significant benefits, including faster patient care, improved data accuracy, and reduced operational costs. These results underscore the potential of HIoT to enhance community-based health services. The study provides a foundation for future research and practical applications. Further investigation will be conducted to evaluate the scalability of the system in diverse communities and its impact on long-term health outcomes.